Seguimento dos pacientes com alergia à proteína do leite de vaca tolerantes aos assados - Afonso, Christiane Pereira e Silva (2020)
Objective: To verify the follow-up of patients who acquired tolerance to baked cow's milk (CM) in relation to allergic tests (specific IgE and SPT CM) and their evolution to tolerance to raw CM, to analyze the prediction of these allergic tests in relation to tolerance to raw CM. Methods: In a university hospital, were evaluated retrospectively, 82 children with allergy to cow's milk protein (CMPA) IgE mediated, retrospectively evaluated, tolerant to baked form, submitted to a raw CM oral food challenge (OFC) were enrolled. Results: Twenty-nine of patients (65.9%) showed tolerance during OFC for raw CM, while 15 (34.1%) continued positive. The average age of group who reached tolerance was 37.38 months (± 26.84), while in the non-tolerant group was 52.27 months (± 34.07). There was a significant difference between the CM specific IgE dosages between these groups in the initial OFC for baked (p:0.0036) and during OFC for raw CM (p:0.0056). Similarly, CM SPT during OFC for raw CM (p<0.0001) was significant. Conclusions: The resolution of milk allergy is associated with specific IgE levels and SPT diameter for CM. We observed through the probability curves that these allergic tests help us in predicting the resolution of the allergy and in deciding whether or not to indicate TPO in this group of patients. After 18 months of eating baked without tolerance to raw CM, the study suggests trying other treatment options for CMPA.